Relationships Between Men and Women in Lithuanian Partisan Movement - Kripienė, Enrika (Genocidas ir rezistencija, 2020)
About postwar armed resistance in Lithuania we used to talk concentrating our attention to the proccess, it‘s development and it‘s circumstences. Most of the work about partisans are from heroic romantic historiography. Their partisans are portraid as fearless warrior, clever politics, sometime tired, making mistakes herois. However attention to the daily life is paid very little. One of those aspects of daily life - relationship between men and women. It is important, interesting, also very difficult and comlicated theme.
Keywords: armed resistance; partisans; women; household